Strategies and tactics of the British parental discourse: historical perspective - Morozova, Iryna; Vakulenko, Anastasia (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2023)
This article studies verbal and non-verbal means of implementing parental discourse strategies and tactics used by representatives of the British linguistic and cultural community of the 18th and 21st centuries and establishes the changes they underwent in the speech of the father’s and the mother’s discursive personality. The research is substantiated by linguists’ growing interest in the ways communicative behaviour is formed, including its diachronic aspects. The research is aimed at establishing characteristic features of British parents and children’s communication basing on British fiction films, whose main characters are typical representatives of the Georgian era (the series “Aristocrats” and “Pride and Prejudice”) and the present (“Broadchurch”). The object of study is the strategies and tactics of the British parental discourse of the corresponding centuries, and the subject is verbal and/or non-verbal variants of their actualization. The study is based on the methods of discursive and contextual analysis, which allowed us to reveal the specifics of typical communicative strategies and tactics functioning in the British parental discourse, and comparative analysis, which contributed to identification of changes of strategies and tactics configuration in the speech of the father’s and the mother’s discursive personality of the 21st century compared to the speech of the father’s and the mother’s discursive personality of the 18th century. We claim that the speech of both the father’s and the mother’s discursive personality in both historical periods is dominated by cooperative strategies with a tendency to a moderate increase in the frequency of use, with the leading strategy for both historical periods being that of cooperation; the leading tactics vary – providing advice and instructions in the 18th century and discussion in the 21st century. Confrontation strategies do not significantly vary in terms of gender and chronological factors either: for both centuries under study, the conflict strategy is the leading one; the dominant tactics for the father’s discursive personality is order, for the mother’s discursive personality it is condemnation/reproach.